IDENTIFIKASI JENIS-JENIS TUMBUHAN BERKHASIAT OBAT DI JALAN PARIT H. HUSIN 2 KECAMATAN PONTIANAK TENGGARA - Fadillah H. Usman; Fathul Yusro; Gusti Eva Tavita; Lolyta Sisillia; Sondang M. Sirait (Tengkawang : Jurnal Ilmu Kehutanan, 2013)
The aim of this research is to identification of medicinal plants in Parit H. Husin 2 street Pontianak Tenggara Subdistrict. Method of the research is documentation part of plants, take some of leaf and species identification in laboratory. The quantity of medicinal plants are 65 species that distribution in 42 family, majority family is Euphorbiaceae (6 species), 50.77% used for both of outside and inside of body, 43.08% used only for inside of body and 6.15% used only for outside of body. Keywords: Identification, medicinal plants, Parit H. Husin 2 street, Pontianak Tenggara Subdistrict